Validation of the names of four species of laelapid mites (Mesostigmata: Laelapidae) parasitic on sigmodontine rodents (Rodentia: Cricetidae) - Lareschi, Marcela; Savchenko, Ekaterina (Zootaxa, 2021)
Savchenko & Lareschi (2019) and Lareschi (2020) described four new species of mites in the family Laelapidae. However, the papers were published in electronic form only and were not registered in ZooBank. They do not satisfy Article 8.5.3 of the International Code of Zoological Nomenclature (ICZN 2012), so the new names are not available from those papers. Therefore, the aim of the present note is to validate the names Laelaps schatzi, Androlaelaps azarae, Androlaelaps montensis and Androlaelaps cursor. Type specimens of the four new species are deposited in the Colección de Entomología, Museo de la Plata, Argentina.